2005
DOI: 10.7326/0003-4819-143-6-200509200-00007
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Chronic Disease Self-Management Programs for Older Adults

Abstract: Self-management programs for diabetes mellitus and hypertension probably produce clinically important benefits. The elements of the programs most responsible for benefits cannot be determined from existing data, and this inhibits specification of optimally effective or cost-effective programs. Osteoarthritis self-management programs do not appear to have clinically beneficial effects on pain or function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
476
3
20

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 676 publications
(516 citation statements)
references
References 80 publications
17
476
3
20
Order By: Relevance
“…Therefore, elderly people will live longer, will thus tend to develop chronic illnesses inherent of the aging process and will more likely need hospitalization. These chronic damages are defined as usually incurable conditions, which call for individual adaptive processes in order to prevent, minimize, and control long-term complications (3) . The Nurses play an important role in the care for chronic patients.…”
Section: Diagnósticos De Enfermagem E Intervenções Prevalentes No Cuimentioning
confidence: 99%
“…Therefore, elderly people will live longer, will thus tend to develop chronic illnesses inherent of the aging process and will more likely need hospitalization. These chronic damages are defined as usually incurable conditions, which call for individual adaptive processes in order to prevent, minimize, and control long-term complications (3) . The Nurses play an important role in the care for chronic patients.…”
Section: Diagnósticos De Enfermagem E Intervenções Prevalentes No Cuimentioning
confidence: 99%
“…In self-management, patients solve their health problems as an active participant (Sohng, Kim, & Cho, 2001). Self-management programmes in the elderly have been studied in people who have diabetes mellitus, hypertension, and osteoarthritis, and it has been proven to improve self-efficacy (Chodosh et al, 2005). However, the development of self-management programmes for fall prevention in the healthy community-dwelling elderly population is currently insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy studies of self-management support have shown improvements in patient satisfaction, healthy behaviors, self-efficacy, and, in some cases, utilization and clinical outcomes (31)(32)(33). However, implementation of self-management support services varies widely (34,35), and these interventions often do not reach the populations that need these services the most (4,(36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%